2015
DOI: 10.1111/crj.12341
|View full text |Cite
|
Sign up to set email alerts
|

Serum Krebs von den Lungen‐6 level as a diagnostic biomarker for interstitial lung disease in Chinese patients

Abstract: Serum KL-6 levels might be a promising diagnostic biomarker for ILDs in Chinese patients. The prognostic value of serum KL-6 levels for ILDs remains to be verified by large-scaled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 30 publications
5
48
0
2
Order By: Relevance
“…As we know, ethnicity differences existed in the clinical manifestations and laboratory results of SSc . To our best knowledge, there was only one study from a Chinese cohort retrieved in Pubmed that probed into the correlation between serum KL‐6 and patients with ILD, and they confirmed the diagnosis value of KL‐6 for ILD patients . Our present cohort was intended to investigate the predictive and prognostic value of serum KL‐6 for Chinese SSc‐ILD patients.…”
Section: Introductionmentioning
confidence: 89%
“…As we know, ethnicity differences existed in the clinical manifestations and laboratory results of SSc . To our best knowledge, there was only one study from a Chinese cohort retrieved in Pubmed that probed into the correlation between serum KL‐6 and patients with ILD, and they confirmed the diagnosis value of KL‐6 for ILD patients . Our present cohort was intended to investigate the predictive and prognostic value of serum KL‐6 for Chinese SSc‐ILD patients.…”
Section: Introductionmentioning
confidence: 89%
“…indicators. Since this is a noninvasive test, KL-6 test has high clinical application value.Hu et al17 reported that, in China, when the cutoff value was set to 500 U/mL, the sensitivity and specificity of KL-6 in ILD diagnosis were 77.75% and 94.51%, respectively. However, recently, literature reports have shown that the cutoff value of serum KL-6 level varies among different races 18,19.…”
mentioning
confidence: 99%
“…Serum KL-6 düzeyinin ‹AH'I olan hastalarda olmayanlara göre daha yüksek oldu¤u gösterilmifltir. [49] ‹AH tan›s› koymak için akci¤er biyopsisi yapmaya gerek yoktur. Ancak radyolojik bulgular tipik de¤ilse veya malignite, enfeksiyon, meslek hastal›¤› gibi nedenleri ekarte etmek için yap›labilir.Transbronflial biyopsi de ‹AH tan›s› için flart de¤il fakat ilaç iliflkili akci¤er hasar›, sarkoidoz ya da enfeksiyonu d›fllamak için yap›lmas› gerekebilir.…”
Section: Risk Faktörleriunclassified